Plasma of electric arc between composite electrodes on silver base - Babich, I.L.; Boretskij, V.F.; Kryachko, L.A.; Minakova, R.V.; Semenyshyn, R.V.; Veklich, A.N. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The investigations of the processes of the mass transfer in a discharge gap of electric arc and peculiarity of interactions of discharge plasma with composite electrode surface were carried out. The optical spectroscopy and metallographic techniques were used. It was found that qualitative change of electric erosion mechanism of electrodes components are realized with increasing of arc current up to 30 A.